Analysis of Motor Vehicle Accidents in Karnataka Between 2008-2017 - Manashree Mane; Ambulu V R; Ajay Kumar. S; Harshavardhan. V; Akhil Navle; Pradeep HV (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Motor vehicle collisions usually result in consequences like property damage, injury and death. Itcausesfinancial losses to the victim himself, families of the victim and to the country. Traffic collision often resultsin injury, death or property damage.Purpose: The objective of the research is to provide a better understanding on motor vehicle accidents that occurredin the time span of 2008-2017 in Karnataka.Procedure: The data obtained was secondary data from report of Ministry of Road Transport and Highways andCEIC Data Global Database website. This data was then categorised under India Premium Database’s AutomobileSector- table IN.RAF018: Road Accidents: Karnataka.Conclusion: From the data obtained it is seen that the rate of Motor vehicle accidents in Karnataka is still growingat a rapid pace.